Fabrication of uniform porosity, all-porous-silicon microstructures and stress/stress gradient control. (21st February 2017) - Sun, Xiao; Parish, Giacinta; Keating, Adrian
Abstract: All-mesoporous silicon microstructures were released with standard micromachining processes. The extremely high porosity of the films allows control of the mechanical properties as well as providing a platform material for devices with extremely large surface area. To pattern and release devices from these highly porous structural layers, pore filling, photoresist mask adhesion and electropolishing techniques were developed. The internal stress of porous silicon was characterized under repeated thermal annealing and HF immersion treatments, allowing a stable, slightly tensile stress of 2.0  ±  0.4 MPa to be achieved. A method to independently control the stress gradient induced curvature in the porous MEMS devices was developed, which achieved released PS structures that were flat to within 78 nm over a range of 100 µ m. This is the first time that fully released, stress gradient adjusted all-mesoporous-silicon structures have been reported.